Trophic interactions may reverse the demographic consequences of inbreeding. Issue 11 (3rd November 2016) - Bompard, Anaïs; Amat, Isabelle; Fauvergue, Xavier; Spataro, Thierry
Abstract: Extinctions have no simple determinism, but rather result from complex interplays between environmental factors and demographic‐genetic feedback that occur at small population size. Inbreeding depression has been assumed to be a major trigger of extinction vortices, yet very few models have studied its consequences in dynamic populations with realistic population structure. Here we investigate the impact of Complementary Sex Determination (CSD) on extinction in parasitoid wasps and other insects of the order Hymenoptera. CSD is believed to induce enough inbreeding depression to doom simple small populations to extinction, but we suggest that in parasitoids CSD may have the opposite effect. Using a theoretical model combining the genetics of CSD and the population dynamics of host‐parasitoid systems, we show that CSD can reduce the risk of parasitoid extinction by reducing fluctuations in population size. Our result suggests that inbreeding depression is not always a threat to population survival, and that considering trophic interactions may reverse some pervasive hypotheses on its demographic impact.